Characteristics and primary productivity of East Antarctic pack ice during the winter-spring transition. (September 2016) - Ugalde, Sarah C.; Westwood, Karen J.; van den Enden, Rick; McMinn, Andrew; Meiners, Klaus M.
Abstract: Microbial communities have evolved mechanisms to allow them to survive within the challenging and changing pack ice environment. One such mechanism may be the exudation of photosynthetically-derived organic carbon into various extracellular pools. During the 2nd Sea Ice Physics and Ecosystems eXperiment (SIPEX-2), East Antarctic pack ice productivity and subsequent carbon allocation were quantified, together with physico-biogeochemical characteristics (29 September–28 October, 2012). Mean ice thickness ranged between 0.80 and 2.16 m, and typically exhibited a warm ice interior with weak temperature gradients. All stations, with one exception, were layered with granular (mean: 78%), columnar (mean: 15%), and mixed granular/columnar (mean: 4%) ice. Highest ice brine-volume fractions were at the ice–water interface, but all ice had high brine-volume fractions conducive for brine percolation (mean: 15%). Dissolved inorganic nutrient concentrations in the brine were scattered around theoretical dilution lines (TDLs), with some values of nitrate and nitrite, ammonium and silicic acid falling below TDLs, indicating nutrient depletion. Bulk ice dissolved organic carbon was low (mean: 64 µmol kg −1 ), but most samples showed enrichment in relation to TDLs. Microbial biomass (bacterial and algal) was low, and generally showed maxima in the sea-ice interior. Bottom ice algal communities were dominated by pennate diatom species (mean: 86% of total cell abundance). 14 C-total primary productivity ( 14 C-TPP) ranged from <0.01 to 2.22 mg C (mg chl a) −1  d −1 (<0.01 to 3.03 mg C m −2  d −1 ). The relative contribution of 14 C-total extracellular organic carbon ( 14 C-TEOC) to 14 C-TPP decreased over the observational period (range: 44–21%), with the remaining proportion being 14 C-particulate organic carbon. 14 C-TEOC composition was dominated by low molecular weight 14 C-extracellular dissolved organic carbon (mean: 61%), with the remaining proportion allocated to 14 C-colloidal organic carbon. Production of 14 C-extracellular polymeric substances was not detected at any station.